(untitled) (The Shivapuri Journal, 2026)
One of the major components of state power is the national army, which is the center of the institutions of all modern polities. The necessity and circumstance shaped the Nepali Army as it pursued modernization, making significant advances during the premiership of Jung Bahadur Rana. This qualitative research work relies on the evidence presented in the historical books, scholarly journals and research articles which are supported with the archival documents of Nepali Army Library. It analyzes the reformation projects of Jung Bahadur concerning the organization, recruitment, training and discipline, manufacturing of arms, infrastructure and administration with references to the military history of Nepal. His policies transformed the army into a centralized institution as it had been a feudal tradition. It strengthened the national defense and concentrated the political power of the country in the nineteenth century Nepal. It ensured internal stability and improved the foreign policy of Nepal. This paper presents the reforms of Jung Bahadur in terms of the modernization theory, and how the process of military modernization helped in strengthening the state and the development of the Nepal’s national identity and strategic independence.